1993
DOI: 10.1111/j.1469-7998.1993.tb01943.x
|View full text |Cite
|
Sign up to set email alerts
|

Annual cycles of migratory fattening, reproduction and moult in European quail (Coturnix coturnix)

Abstract: Experimental studies of the physiological mechanisms underlying avian migration have concentrated on small passerines. The present study is concerned with the regulation of migratory fat deposition in a galliform. the European quail (Coturnix coturnix). The increased mass associated with migration was due exclusively to the deposition of fat whereas the increased body mass of laying females was due to increases in lean tissue and water as well as fat. Annual cycles of body mass, moult, gonadal size and plasma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 40 publications
3
25
0
Order By: Relevance
“…However, castration at this juncture increased diurnal activity, as noted previously in domestic fowl, Japanese quail, white-throated sparrows, GWCS, and goldencrowned sparrows (Zonotrichia atricapilla) (Boswell et al, 1993;Morton and Mewaldt, 1962;Weise, 1967). Such findings have been correlated with elevated body temperature measured during the day in castrated Japanese quail over intact controls (Feuerbacher and Prinzinger, 1981;Hanssler and Prinzinger, 1979).…”
Section: Effects Of Castration On Short Day Lengthssupporting
confidence: 48%
See 3 more Smart Citations
“…However, castration at this juncture increased diurnal activity, as noted previously in domestic fowl, Japanese quail, white-throated sparrows, GWCS, and goldencrowned sparrows (Zonotrichia atricapilla) (Boswell et al, 1993;Morton and Mewaldt, 1962;Weise, 1967). Such findings have been correlated with elevated body temperature measured during the day in castrated Japanese quail over intact controls (Feuerbacher and Prinzinger, 1981;Hanssler and Prinzinger, 1979).…”
Section: Effects Of Castration On Short Day Lengthssupporting
confidence: 48%
“…Whereas a pulse of testosterone temporarily increased CPL and muscle hypertrophy, it failed to affect a continuous prenuptial molt and migratory restlessness. Thus, it is possible that 1) the transient pulse of testosterone is necessary but not sufficient for full development of the migratory phenotype, but that the testosterone pulse only primes central functions for further actions of both photoperiod and reproductive hormones that are secreted later in the spring or 2) the transient pulse of testosterone is neither sufficient nor necessary for the full migration phenotype and that continuous uninterrupted secretions from the gonad might be critical for the full expression to develop or 3) that timing of the organizational effects of T occurs earlier in the fall as suggested by Boswell et al (1993) and Thapliyal et al (1983). Previous studies have identified autumnal androgen in European quail (Coturnix coturnix coturnix), white-throated sparrows (Zonotrichia albicollis) and, Rouen duck (Anas paltyrhynchos) (Balthazart, 1983;Balthazart and Hendrick, 1976;Boswell et al, 1993Boswell et al, , 1995aSchlinger, 1987) and more recently in field studies on GWCS (M. Ramenofsky, Z. Németh, J. Krause, unpublished data).…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Presumably, there is no decrease in the cGnRH-I secretion at this time, so again, the presumption must be that synthesis of cGnRH-I resumes, or at least increases. Relative photorefractoriness has only been formally characterized in one domesticated species, the Japanese quail (Robinson & Follett 1982); the wild subspecies, the European quail (Coturnix coturnix), appears to show identical photoperiodic responses (Boswell et al 1993). In quail, the gonads remain mature indefinitely if birds are kept on a long photoperiod.…”
Section: The Basic Physiological Templatementioning
confidence: 99%